Biodiversity conservation in Asean emerging issues & regional needs - Murtedza Mohamed; Ghazali Ismail (ASEAN Academic Press, 1998)
In this book, renowned scientists and policymakers in Asean countries argue that each country has taken mindful approaches to addressing their specific and unique environmental and biodiversity conservation issues.